2015
DOI: 10.3329/bjnm.v17i1.22491
|View full text |Cite
|
Sign up to set email alerts
|

Radiation exposure levels in close proximity to therapeutic patients treated for thyroid carcinoma with high dose I-131

Abstract: High dose I-131 therapy is administered to thyroid cancer patients after thyroidectomy. In the treatment process when a radiopharmaceutical is administered to patients, they become a mobile source of radiation. After the treatment, contamination may arise from large amount of activity, which is excreted during the period of hospitalization . To reduce the rate of exposure it is essential to monitor workplace. This study determines the rate of radiation exposure in the room where the patient stays during the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…John E.E et al reported 21.72 µSv/hr in the toilet bowls used by radiopharmaceuticals injected patients in nuclear medicine facility of Ibadan [19]. Ferdoushi Begum et al observed dose rate in toilet room was found high (22-110 µSv/hr), in the corridor, the dose rate was 3.4-18 µSv/hr and next to isolation room 0.3-16 µSv/hr for the thyroid carcinoma patients treated with high dose of RAI in Dhaka [25]. Another study conducted by Wirote Changmuang at Ramathibodiûs hospital for Admitted Thyroid Cancer Patient with High Dose I-131 Treatment in Related Hospitalized Area reported the exposure around the patient bed between 11.86-51.41 μSv/h [26].…”
Section: Resultsmentioning
confidence: 99%
“…John E.E et al reported 21.72 µSv/hr in the toilet bowls used by radiopharmaceuticals injected patients in nuclear medicine facility of Ibadan [19]. Ferdoushi Begum et al observed dose rate in toilet room was found high (22-110 µSv/hr), in the corridor, the dose rate was 3.4-18 µSv/hr and next to isolation room 0.3-16 µSv/hr for the thyroid carcinoma patients treated with high dose of RAI in Dhaka [25]. Another study conducted by Wirote Changmuang at Ramathibodiûs hospital for Admitted Thyroid Cancer Patient with High Dose I-131 Treatment in Related Hospitalized Area reported the exposure around the patient bed between 11.86-51.41 μSv/h [26].…”
Section: Resultsmentioning
confidence: 99%